Relevance of Vocational High School Curriculum with the Industrial Needs of Making Batik Competences - Widiaty, Isma (INVOTEC, 2019)
This study aimed to identify the relevance of vocational high school curriculum with the industrial needs particularly related to batik making competences. The data collection was carried out through a survey to 35 batik industries within Priangan area, West Java province, Indonesia. The instrument employed was a questionnaire consisting of batik making competence units based on Standar Kompetensi Kerja Nasional Indonesia (SKKNI), Indonesia National Performance Competence Standards. The respondents of the study were owners of the batik industries requested to measure competence standards on SKKNI in relation to the competences needed within batik industry. The results of the study showed that in general, the competences on the SKKNI taught in vocational high schools were relevant to the competences needed in the industry. There were a few competences classified irrelevant which were Canting and stamping tools. The findings indicated that the competences taught in the schools are in accordance with the standards set in the SKKNI. It is expected that teachers are able to strengthen the competences taught in schools and regularly coordinate with the industry to keep the curriculum updated.